Antioxidant Effect of Curcumin on the Body Weight of Male Albino Wistar Rats Exposed to Pyrethroid Based Mosquito Vaporizers Fumes: An Experimental Study - Yadav , Swati; Dewan, Rakesh Kumar; Rani, Anita; Chopra , Jyoti (Innovations in Biological Science Vol. 5, 2024)
Introduction: Pyrethroid based mosquito vaporisers are commonly used as Personal Protective Measures (PPM) to avoid mosquito-borne diseases. Effective control of mosquito-borne diseases with the use of general public health measures is yet to be achieved in our country, so there is increasing use of PPM like mosquito coils, liquid vaporisers, mats, and insecticide-treated bed nets in the Indian population but data regarding the safety profile of PPM is still scarce. Curcumin is the main biologically active phytochemical component of turmeric. Extensive studies within the last half a century have demonstrated the protective action of curcumin in almost all the disorders of the body. The molecule is known to possess anti-oxidative, anti-inflammatory, antimicrobial, anti-cytotoxic and many other useful properties. The molecule is known to possess neuroprotective properties as well [1]. Aim: To analyse the change in the body weight of male albino wistar rats exposed to pyrethroid based mosquito vaporizers and the protective role of turmeric with withdrawal effect. Materials and Methods: This was an experimental study on a total of 24 male albino Wistar rats from July 2015 to October 2016. They were randomly divided into groups I, II, III and IV. Each group contained six rats. Group I animals served as control, Group II animals were exposed to mosquito vaporiser, 8 hours/day for six days in a week for 90 days, Group III received the same treatment as group II and thereafter retained for 4 weeks of withdrawal to see the reversal changes and Group IV is exposure along with turmeric administration in a dose of 20mg/kg body weight orally. The data was analysed using Statistical Package for Social Sciences (SPSS) version 21.0. Comparison of body weight among different groups at different time intervals is done by paired t-test. A p-value less than 0.05 was considered to be significant. Results: Pyrethroid exposure results in reduced weight gain in exposed group rats. The mean difference in body weight between groups I and II, I and III and I and IV at the end of study was 37.32±24.47gm (p=0.443), 42.02±24.47gm (p=0.343) and 8.29±25.67gm (p=0.988). Weight gain in all the group rats was almost similar till the 8th post-exposure week, after that from the 9th week onwards decremented trend in weight was seen in groups II and III but the group IV rats showed an increasing trend in weight gain. Conclusion: The assessment suggests that inhalation of pyrethroid based mosquito vaporisers fumes has toxic effects, reflected as reduced weight gain following subchronic exposure and one-month withdrawal is not a sufficient time to overcome the damage induced by pyrethroids. Turmeric shows a protective effect which is reflected in the form of weight gain.